Determining star formation rates in AGN hosts from strong optical emission lines - Mellos, Maitê S. Z. de; Riffel, Rogemar A; Schimoia, Jaderson S; Rembold, Sandro B; Riffel, Rogério; Storchi-Bergmann, Thaisa; Wylezalek, Dominika; Ilha, Gabriele S; Albán, Marco; Dors, Oli L; Gatto, Lara; Krabbe, Angela C; et al. (Monthly notices of the Royal Astronomical Society, 2024)
The influence of Active Galactic Nuclei (AGN) on star formation within their host galaxies remains a topic of intense debate. One of the primary challenges in quantifying the star formation rate (SFR) within AGN hosts arises from the prevalent assumption in most methodologies, which attribute gas excitation to young stars alone. However, this assumption does not consider the contribution of the AGN to the ionization of the gas in their environment. To address this issue, we evaluate the use of strong optical emission lines to obtain the SFR surface density (Sigma SFR AGN) in regions predominantly ionized by an AGN, using a sample of 293 AGN hosts from the MaNGA survey, with SFR measurements available through stellar population fitting. We propose calibrations involving the H alpha and [O iii] lambda 5007 emission lines, which can be used to determine Sigma SFR AGN, resulting in values consistent with those estimated through stellar population fitting.
Veröffentlicht: 11 October 2024
Gesehen am 09.04.2025